Die Konstruktion des kulturell Fremden in Peter Handkes Die Morawische Nacht - Glišič, Miša (Vestnik za tuje jezike, 2016)
The article, based on the story The Morawian Night by Peter Handke, attempts to explain divergent cultural phenomena within the social system in the form of relational concepts of "selfhood" and "otherness". The focus is on the search of an individual's own identity in the multicultural setting of Europe. The author, who identifies himself with the protagonist, speaks in existential terms about the cultural dimension of his own experience in intercultural dialogue. With the awareness of otherness and foreignness, he moves among cultures and perceives the cultural dimensions of hybridity. The division of one's self is exemplified with aesthetic experiencing of alienation, and the dilemma between what is one's own and what is foreign. The analysis of philosophical thoughts, behaviour samples, and interpersonal communication make it possible to understand foreignness, which has a crucial role in understanding one's belonging in the cultural process.
Keywords: Handke, Peter, 1942-; "Die Morawische Nacht"; Literarne študije; avstrijska književnost; pripoved; literarni diskurz; medkulturnost; tujost; identiteta